2005
DOI: 10.1016/j.scitotenv.2004.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Use of mineral magnetic concentration data as a particle size proxy: A case study using marine, estuarine and fluvial sediments in the Carmarthen Bay area, South Wales, U.K.

Abstract: Compositional (non-magnetic) data can correlate strongly with particle size, which deems it appropriate as a particle size proxy and, therefore, a reliable means of normalising analytical data for particle size effects. Previous studies suggest magnetic concentration parameters represent an alternative means of normalising for these effects and, given the speed, low-cost and sensitivity of the measurements may, therefore, offer some advantages over other compositional signals. In this work, contemporary sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 65 publications
1
38
1
2
Order By: Relevance
“…Zhang et al [16] suggested that both percentage frequency-dependent magnetic susceptibility (χ FD% ) and χ ARM can be used as a proxy for clay content. However, more recently, Booth et al [9] suggested χ LF , χ ARM and SIRM have potential as a particle size proxy for particular sedimentary environments, but highlight the importance of fully determining the nature of the relationship between sediment particle size and magnetic properties before applying mineral magnetic data as a size proxy. (r = 0.82), χ ARM (r = 0.94) and SIRM (r = 0.81).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [16] suggested that both percentage frequency-dependent magnetic susceptibility (χ FD% ) and χ ARM can be used as a proxy for clay content. However, more recently, Booth et al [9] suggested χ LF , χ ARM and SIRM have potential as a particle size proxy for particular sedimentary environments, but highlight the importance of fully determining the nature of the relationship between sediment particle size and magnetic properties before applying mineral magnetic data as a size proxy. (r = 0.82), χ ARM (r = 0.94) and SIRM (r = 0.81).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the extent to which particular magnetic concentration parameters can be used as a particle size proxy for urban street dust and, secondly, whether theses data associations follow the predictable trends of other environmental studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…All samples were subjected to the same textural preparation and analysis procedure (Booth et al 2005a), using sieving followed by laser diffraction analysis. Low Angle Laser Light Scattering (LALLS), using a Malvern (Mal-vern, England) Mastersizer Long-bed X with a MSX17 sample presentation unit, enabled rapid measurement of particle sizes within the 0.1-2000 µm range.…”
Section: Textural Analysesmentioning
confidence: 99%
“…Based on these investigations, mineral magnetic measurements have been identified as a suitable proxy for geochemical, radioactivity, organic matter content and particle size data (Bonnett et al 1988;Oldfield et al 1993;Hutchinson and Prandle 1994;Clifton et al 1997Clifton et al , 1999Xie et al 1999Xie et al , 2000Zhang et al 2001;Booth et al 2005a;Shilton et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…fluvial [4]; lacustrine [5]; desert [6]; glacial [7]; estuarine [8]; coastal [9] and soils [10]). Compared with other analytical methods mineral magnetics provides a compositional tool, which is reliable, rapid, non-destructive, inexpensive and sensitive to low detection levels [11].…”
Section: Introductionmentioning
confidence: 99%